MOLECULAR INTERACTION BETWEEN BENZONITRILEAND HEXAMETHYLPHOSPHORIC TRIAMIDEBY 13CNMR T1RELAXATIONTIME STUDIES ANDAS INITIOQM CALCULATIONS: EXTENDED INVESTIGATION - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
ABSTRACT It has been obtained the anisotropy ratio a = Tdortho-,meta-13C)/Tdpara-13Co)f dilute solutions of bn change from 1.7 in fa solution and 1.5 in neat bn to 1.0 in HMPT. Thus the anisotropyratio comes out to be a = 1. In HMPT, obviously, solvent molecules cluster around Ph-C=N in such a way, that non-covalent interactions lead to isotropic reorientational motion like a spherical molecule. To conform with the T1times, a layer arrangement with at least two HMPT molecules per Ph-C=N seems to be likely. From computational quantum calculations of non-covalent intermolecular interactions and Mie potential analysis, the solute-solventmolecularpairs in bn.. .HMPThave almost equal interaction energies for the ortho, meta, and para configuration and the layered configurations are energeticallypermitted Keywords: 13CT1spin-lattice relaxation times, ab initio quantum chemistry calculations, intermolecular interactions, isotropic and anisotropic rotational motion